Policy Networks in Community-Based Tourism Management - Musdah, Erwin; Nurdiansyah Nurdin, Wahyu; Asmarianti, Asmarianti (Indonesian Association for Public Administration (IAPA), 2024)
In recent years, tourist villages in Indonesia have experienced significant growth, reaching a total of 4,235 villages by 2022. This growth aims to enhance the local economy and preserve cultural potential. While tourist villages positively impact the economic, social, and environmental sectors, they also produce negative effects such as waste accumulation and economic disparities. To address these issues, community-based tourism (CBT) development has been proposed as an alternative, involving local communities in the management and budgeting of tourist villages. This study employs a qualitative descriptive method to analyze policy networks in the development of community-based tourism in South Sulawesi. Data were collected through in-depth interviews, observations, and document studies in two tourist villages with distinct characteristics: Ara Tourist Village and Latimojong Tourist Village. The findings indicate that the policy network in Ara Tourist Village is larger but centralized around the village government, while in Latimojong Tourist Village, it is smaller and focused on the Community Awareness Group (Pokdarwis). The policy networks in both villages remain concentrated in a single area, limiting community participation from other regions. This research highlights the importance of expanding policy networks to reduce economic disparities between communities in tourist areas and those not adjacent to tourist sites.